Rethinking Islamic legal modernism : the teaching of Yusuf al-Qaradawi - Shaham, Ron. (Studies in Islamic Law and Society, 2018)
In Rethinking Islamic Legal Modernism Ron Shaham challenges the common opinion that Islamic legal modernism, as represented by Rashid Rida (d. 1935), is of poor intellectual quality and should not be considered an authentic development within Islamic law. The book focuses on the celebrated Sunni jurist, Yusuf al-Qaradawi (b. 1926), whom Shaham perceives as a close follower of Rida. By studying the coherence of Qaradawi's Wasati theory of ijtihad and the consistency of its application in his legal opinions (fatwas), Shaham argues that Qaradawi, by means of eclecticism and synthesis, conducts a bold dialogue with the Islamic juristic heritage and brings it to bear on modern developments, in particular the institutional framework of the nation-state.